2007
DOI: 10.1016/j.jpaa.2006.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Jumps in cohomology and free group actions

Abstract: A discrete group G has periodic cohomology over R if there is an element in a cohomology group cup product with which it induces an isomorphism in cohomology after a certain dimension. Adem and Smith showed that if R = Z, then this condition is equivalent to the existence of a finite dimensional free-G-CW-complex homotopy equivalent to a sphere. It has been conjectured by Olympia Talelli, that if G is also torsion-free then it must have finite cohomological dimension. In this paper we use the implied condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 11 publications
(18 reference statements)
0
21
0
Order By: Relevance
“…In [26], we have shown that HL \ J Z D H 1 L. Combining this together with Proposition 4.6 implies HL \ H cell 1 .P Z / D H 1 L: (a) In Section 3, we pointed out that the group L @ !…”
Section: Remark 33 Note That Over the Integers Part (B) Of The Lemmentioning
confidence: 86%
See 2 more Smart Citations
“…In [26], we have shown that HL \ J Z D H 1 L. Combining this together with Proposition 4.6 implies HL \ H cell 1 .P Z / D H 1 L: (a) In Section 3, we pointed out that the group L @ !…”
Section: Remark 33 Note That Over the Integers Part (B) Of The Lemmentioning
confidence: 86%
“…In [26], we considered a new (co)homological condition for groups called jump (co)homology. In this section, we take a closer look at groups with this property.…”
Section: Jump (Co)homologymentioning
confidence: 99%
See 1 more Smart Citation
“…I thank the referee for comments, and particularly for calling my attention to the two papers of N. Petrosyan which contain related results [3,Propsition 1.3] and [4,Theorem 4.2] which are proved in similar way. I thank J. Kollár for drawing my attention to such problems (see Section 3).…”
Section: Introductionmentioning
confidence: 92%
“…Until the recent work [ABJ 09], where groups with a strong global fixed point property are constructed, the only way to show that a group G did not belong to HF was to find a subgroup of G isomorphic to the Thompson group F. Here we show that certain branch groups, such as the first Grigorchuk group G is not contained in the class HF. Furthermore, G is a counterexample to a conjecture of Petrosyan [Pet07] and answers in negative a question of Jo-Nucinkis [JN08].…”
Section: Introductionmentioning
confidence: 99%